EFEKTIVITAS PENERAPAN SISTEM INFORMASI KEPEGAWAIAN DI KABUPATEN TASIKMALAYA - Andi Andi (LPPM STIA Banten, 2021)
The background of the problem in this study is that there are still obstacles in the implementation of the personnel information system, namely in the adaptation of its management which requires skills and mastery of computer information technology and there is still a large amount of data that has not been updated in an electronic-based information system. The research method used is descriptive with a qualitative approach in which the informants are the Head of the Personnel and Human Resources Agency and ASNs in each Tasikmalaya Regency Regional Apparatus Organization who are responsible for managing the personnel information system. The results of the study show that the implementation of the personnel information system in the Tasikmalaya Regency government office environment has been running effectively, but there is still something that needs to be improved in terms of management adaptation and there are still a lot of staffing data that have not been updated which can hinder work.